Risks of using digital technologies in the activities of local government bodies - M. A. Lipchanskaya; S. E. Channov; A. Yu. Churikova (Правоприменение, 2024)
The subject. The article analyzes the existing practice of implementation and use of digital technologies at the municipal level. The choice of the research object is conditioned by the fact that currently most acts in the field of digitalization of public authority affect the federal or regional level, meanwhile, the digital transformation of local self-government has its own specificity, due to the peculiarities of this level of social management, which should be taken into account in the legal regulation.The purpose of the study: identify the risks that have a negative impact on the process of digital transformation of local governance, and propose measures to minimize or eliminate the identified risks by legal means.Methodology. The research utilized integrated and interdisciplinary approaches. The methodological basis of the study was formed by a set of methods of cognition, the main of which were: methods of formal and dialectical logic and analysis, comparative-legal and system-structural methods, as well as sociological methods of research.Conclusions. The following conclusions were made based on the results of the research:1.The main risks of introducing digital technologies in the activities of local government are: the risk of violating the security and confidentiality of personal data of citizens during their processing and storage in the digital systems of local government; the risk of cyberattacks, hacking or unauthorized access to information systems operated by municipal authorities; the risk of insufficient legal regulation of the introduction and use of digital technologies; the risk of using inappropriate or low-quality digital technology.2.The following measures are proposed as measures to minimize the identified risks: systematic mandatory informing of both local government officials and the public on the correct procedure and liability measures for the implementation and operation of digital technologies, transmission, storage and processing of personal data, etc., which will contribute to the formation of the necessary level of legal literacy; revision of the system of penalties for deliberate violations in the field of operation of digital technologies by local government officials; organize control over the acts adopted by local government bodies with the involvement of the population and the use of digital technologies to receive feedback from the population on the acts adopted by local government bodies; develop and consolidate the principles and procedures for the introduction and use of end-to-end digital technologies in the activities of state and municipal authorities; provide for the possibility of revising any decision made in case of a technical failure that occurred in the course of the decision-making process; provide for the use of digital technologies in the activities of state and municipal authorities; and provide for the use of digital technologies in the activities of local government bodies.